Block freeze concentration assisted by centrifugation applied to blueberry and pineapple juices. (August 2015) - Petzold, Guillermo; Moreno, Jorge; Lastra, Paz; Rojas, Katerin; Orellana, Patricio
Abstract: Centrifugation is an alternative assisted technique to improve the efficiency of block freeze concentration. In this study reported the centrifugation to enhance the separation of concentrated solution from frozen fruit juices (blueberry and pineapple) in three cryoconcentration cycles. To force the separation of solutes from the frozen samples we used a centrifuge operated for 10 min at 20 °C and 4600 rpm. This technique has good performance after the third cycle, reaching an increase of approximately 2.5 times the initial concentrations of solids, values close to 0.74 kg solute per 1 kg initial solute, and approximately 60% of the percentage of concentrate. The performance of block freeze concentration assisted by centrifugation applied to fruit juices was attributed to ice matrix acting as a porous solid through which the concentrated solution percolates through drainage channels of the ice improved by the centrifugal force. Industrial relevance: The block freeze concentration allows producing food concentrates with high quality when thawed a frozen solution assisted or not by a technique to enhance the separation efficiency. In this work has applied centrifugation as an assisted technique to improve the efficiency of block freeze concentration applied to fruit juices, obtaining promissory results. Highlights: We use the centrifugation for separating the concentrate from frozen juices. This technique has high performance after the third cryoconcentration cycle. The concentrated solution percolates through drainage channels of the ice.